ANALISIS REPRESENTASI KELAS SOSIAL DALAM FILM SNOWPIERCER (2013) DAN MANFAATNYA DALAM PEMBELAJARAN SOSIOLOGI DI SMA - Kasim, Hasanudin; Nur, Hasruddin; Amir, Arfenti; Jalal, Jalal; Sriwahyuni, Sriwahyuni (Universitas Negeri Makassar, 2024)
Abstract. This research aimed to analyze and describe the representation of social class in the Snowpiercer (2013) and its benefits to study sociology in senior high school. The type of approach in this research was a qualitative descriptive method with the Snowpiercer (2013) as the data source. The data collection technique used documentation technique. Data analysis was content analysis by applying the Miles and Huberman model. The research results show that the representation of social class was very dominant and played an important role in the plot and narrative of the Snowpiercer (2013), including: a) upper class vs lower class; b) exploitation and oppression; c) resistance and revolution; d) visual symbolism; e) upper class decadence; and f) manipulation of information. Then, the benefits of the Snowpiercer (2013) in studying sociology of senior high school including: visualizing social structure in learning material, visualizing social inequality in learning material, visualizing diversity and identity in learning, and visualizing rebellion and social change in learning.Abstrak. Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan representasi kelas sosial dalam Snowpiercer (2013) dan manfaatnya dalam pembelajaran sosiologi di SMA. Jenis pendekatan pada penelitian ini merupakan pendekatan kualitatif metode deskriptif analisis dengan objek Snowpiercer (2013) sebagai sumber datanya. Teknik pengumpulan data yaitu teknik dokumentasi. Analisis data adalah analisis isi dengan menerapkan model Miles dan Huberman. Hasil penelitian menunjukan bahwa representasi kelas sosial sangat dominan dan memainkan peran penting dalam plot dan narasi Snowpiercer (2013) antara lain: a) kelas atas vs kelas bawah; b) eksploitasi dan penindasan; c) perlawanan dan revolusi; d) simbolisme visual; e) dekadensi kelas atas; dan f) manipulasi informasi. Kemudian adapun manfaat Snowpiercer (2013) dalam pembelajaran sosiologi di SMA antara lain: memvisualisasikan struktur sosial dalam materi pembelajaran, memvisualisasikan ketimpangan sosial dalam materi pembelajaran, memvisualisasikan diversitas dan identitas dalam pembelajaran, dan memvisualisasikan pemberontakan dan perubahan sosial dalam pembelajaran.